(untitled) (International Journal of Engineering and Computer Science, 2016)
Rendering reliable and efficient communication along with security under losing channels is one among the major technical challenges in wireless network, especially in industries with vital and severe environments. In this task, illustrated a scheme to raise the resilience to link dynamics for Wireless Web, R3E is designed to enhance existing reactive course-plotting protocols to provide reliable and energy-efficient packet delivery against the unreliable cordless links by utilizing the local path diversity. Security is the major challenge with the R3E approach. Security with R3E is to be rendered with the range of the threshold, calculated at every node in the network. Proposed mechanism confirms reliable and secure path from source to destination by removing malicious nodes in the network